THE IMPACT OF CYBER-GENRE ON LANGUAGE AND LITERACY - Endang Hartiningsih (Universitas Stikubank (UNISBANK) Semarang, 2008)
New cyber-genres such as emails and web pages have long been generated by the interaction of people through the discourses of business, government, and media. When at the moment schools have access to expertise in the advancement of Information technology, the interaction of schools and the internet is also enhanced. The paradigm creates a new practice in the use of language and literacy. Positive attitude of English teachers, experts in English education and information technology, and the government towards the new paradigm should critically be formulized. Therefore, this paper tries to provide some annotation on how the new literacy practice could be facilitated to students. Key Word: cyber-genres, literacy